Hydrogen production by the Ruthenium(II) complex bearing a bulky PNP ligand: a catalyst for the decomposition of formic acid and/or ammonium formate - Bogado, André Luiz; Paschai Darian, Leon K.; Bürgy, David; dos Santos, Lucas da Silva; Ueno, Leonardo Tsuyoshi (ACS omega, 2024)
The five-coordinate complex [RuCl2(PNP)] (1) was synthesized from the binuclear [RuCl2(p-cym)]2 with a PNP-type ligand (PNP = 3,6-di-tert-butyl-1,8-bis(diisopropylphosphino)methyl)-9H-carbazole - (CbzdiphosiPr)H) in a toluene solution, within 20 h at 110 °C, producing a green solid, which was precipitated with a 1/1 mixture of n- pentane/HMDSO. The complex was characterized by NMR─1H, 13C, and 31P{1H}, mass spectroscopy─LIFDI, FTIR, UV/vis spectroscopy, and cyclic voltammetry, as well as a description of the optimized structure by DFT calculation. The reactivity of 1 was investigated in the presence of potassium triethylborohydride (KBEt3H, in THF solution of 1.0 mol L-1) and ammonium formate (NH4HCO2), producing an in situ hydride complex and a formate intermediate species coordinated to the ruthenium center. The complex 1, loaded with 0.08%, catalyzed the decomposition of ammonium formate (AF) into H2, CO2, and NH3 in THF solutions at 80 °C, with 94% of H2 and TOF = 206 h-1 (molar ratio [Ru]/AF = 1/1204). The catalytic activity increased remarkably for the decomposition of formic acid (FA) as a substrate to produce H2 and CO2. In the HMDSO solution at 80 °C, a conversion of 100% was obtained in relation to H2 and TOF = 3010 h-1 (molar ration [Ru]/FA/NEt3 = 1/1204/843). In an equimolar mixture of AF/FA in HMDSO solution at 80 °C, without additives, the complex 1 catalyzed the decomposition of both with 100% of H2 and TOF = 987 h-1 (molar ratio [Ru]/AF/FA= 1/602/602). Under the later conditions, as well as upon AF decomposition, carbamic acid [HO(C═O)NH2] was obtained as a coproduct of a secondary reaction between NH3 and CO2 (yield = 50% in relation to the amount of AF). A kinetic study for decomposing FA, in the range of 60-100 °C, provided ΔS‡ = −9.7 e.u, ΔG‡ = 13.35 kJ mol-1, and Ea = 64 kJ mol-1, suggesting that the mechanism is more associative than for the known complexes.